PENGARUH HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI STARBUCKS SUNSET STAR BALI - Tholibin, Ahmad Sirojut; Wardana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Customer satisfaction is the best guarantee to create and maintain customer trust to face global competition. The company's success in maintaining customer loyalty is influenced by many factors including: service quality, either directly or mediated by increasing the role of trust, commitment and customer satisfaction. This study aims to analyze the effect of price, promotion and quality policies on customer satisfaction at Starbucks Coffee Shop products and services at Sunset Star. The type of research used in this research is a survey. In survey research, information is collected from respondents using a questionnaire. The data analysis technique used in this research is regression analysis technique. The sample of this research is Starbucks Sunset Star Branch, Bali. The results of this study indicate that of the three variables used, only the price variable dominates the influence on customer satisfaction at Starbucks Sunset Point. Therefore, it is necessary to do further research to obtain variables that can affect customer satisfaction at Starbucks Sunset Point.